Impact Of Electronic Word Of Mouth On Purchase Intention Of Skintific Products Via Tiktok - Muhammad Ibnoe Nugraha; Satria Bangsawan; Dorothy Rouly H. Pandjaitan (Cita konsultindo, 2025)
This study aims to examine the influence of electronic word of mouth (eWOM) on purchase intention toward Skintific products on the TikTok platform. The primary objective is to analyze how consumer perceptions of information quality, information quantity, and information adoption derived from TikTok content can shape their intention to purchase skincare products. This research employs a quantitative method with a survey-based approach, using a structured questionnaire as the instrument for data collection. The questionnaire was distributed to TikTok users who had viewed or been exposed to Skintific-related content. The data were analyzed using multiple linear regression. The findings reveal that information adoption has a significant positive effect on purchase intention, whereas information quantity does not significantly influence perceived information usefulness. These results suggest that the relevance, usefulness, and credibility of information are more critical than its sheer volume in influencing consumer decision-making. Moreover, the process by which users adopt information from TikTok plays a central role in shaping favorable perceptions that ultimately lead to purchase intention.